2017
DOI: 10.1016/j.jvs.2016.08.106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of single or double tibial artery revascularization in critical limb ischemia patients with tissue loss

Abstract: The achievement of double vessel inflows to the wound by double tibial artery revascularization positively affects wound healing, particularly in severe CLI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…They concluded that the achievement of double vessel inflows to the wound by double tibial artery revascularization positively affects wound healing, particularly in severe CLTI patients. 49…”
Section: Single or Multivessel Infrapopliteal Revascularization: Whatmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the achievement of double vessel inflows to the wound by double tibial artery revascularization positively affects wound healing, particularly in severe CLTI patients. 49…”
Section: Single or Multivessel Infrapopliteal Revascularization: Whatmentioning
confidence: 99%
“…First, due to the high restenosis rate typical of infrapopliteal vessel angioplasty a multiple vessel approach could provide enduring wound healing; even if restenosis occurs in one vessel, the perfusion from the other vessel could compensate. 49,51 Second, a multivessel recanalization could provide greater perfusion to the wound, improving healing speed. Perfusing the foot with 2 or 3 arteries could compensate for an incomplete pedal arch, improving wound healing and limb salvage.…”
Section: Single or Multivessel Infrapopliteal Revascularization: Whatmentioning
confidence: 99%
“…Kobayashi et al 33 recently reported that revascularization of both the anterior and posterior tibial arteries, as opposed to single inflow revascularization to either artery alone, resulted in superior outcomes. In double-inflow-treated patients, the wound healing rate was higher, repeat intervention rate lower, and the time to wound healing shorter.…”
Section: Multiple Inflowmentioning
confidence: 99%
“…Whether a single vessel or multiple vessels intervention in the below-the-knee lesion is the optimal endpoint in chronic limb-threatening ischemia (CLTI) patients is still controversial. 14,15 Asian multidisciplinary consensus statement of CLTI management suggested that the goal of intervention for symptomatic isolated infrapopliteal artery diseases should be established at least 1 straight-line flow to the foot. 16 In addition, if technically feasible, a strategy to reconstruct as many arteries as possible is practical because this strategy can certainly provide robust blood flow to a severely ischemic foot and may enhance wound healing.…”
Section: Discussionmentioning
confidence: 99%